Switch to aflibercept in the treatment of neovascular age-related macular degeneration: 30-month results - Ertan,Elif (2021)
ABSTRACT Purpose: This study was conducted to evaluate visual function and changes in the central macular thickness of patients with unresponsive neovascular age-related macular degeneration who were switched from ranibizumab (Lucentis®) to aflibercept (Eylea®) treatment at 30 months. Methods: This retrospective study examined patients with neovascular age-related macular degeneration who were switched to aflibercept after ≥6 previous intravitreal ranibizumab injections at 4- to 8-week intervals. All patients were switched to intravitreal aflibercept (2.0 mg) and analyzed after 3 consecutive injections followed by a prore nata dosing regimen and after 30 months of treatment. Best corrected visual acuity, biomicroscopic examination, intraocular pressure, fundus examination, and central macular thickness were recorded at the start of treatment, before the transition to intravitreal aflibercept treatment, and at 6, 12, 18, 24, and 30 months of intravitreal aflibercept treatment. Results: A total of 33 eyes met the inclusion criteria. The median age of the patients was 73.57 ± 7.98 years, and 21 (61.8%) patients were males and 12 (35.3%) were females. Before the transition, the patients received a mean of 16.8 ± 8.8 ranibizumab injections (range 6-38).After the transition to intravitreal aflibercept treatment, the mean number of aflibercept injections was 9.09 ± 3.94. No significant differences were observed in best corrected visual acuity after the aflibercept switch in any of the months. The central macular thickness was significantly decreased at 6, 12, 18, and 30 months (p=0.01, p=0.03, p=0.05, p=0.05, p<0.001, respectively). Conclusion: Patients with neovascular age-related macular degeneration who were switched to intravitreal aflibercept treatment due to unresponsiveness to intravitreal ranibizumab exhibited a significant anatomic improvement in the retina, and although this state persisted, there was no significant functional gain.